Conservation-Restauration de la peinture sous verre « Digitale » d’Auguste Scévenels - Adeline Vanryckel (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This research focuses on the conservation-restoration of a reverse glass painting produced by Auguste Scévenels. This artwork presents alterations in the glass support. The objective is to propose firstly a method of assembly and secondly to use an innovative technology for the restoration of the glass panel : UV polymerisation adhesives.